STUDI JALUR PENDAKIAN SENARU DAN SEMBALUN TAMAN NASIONAL GUNUNG RINJANI PROVINSI NUSA TENGGARA BARAT - Agil Ramanda Raytodi; Khairun Nisa; Asysyifa Asysyifa (Universitas Lambung Mangkurat, 2020)
The purpose of this research is to know the perception of the level of satisfaction of tourists climbing routes, access and facilities in Senaru and Sembalun regions hiking paths. Methods in this study using the method of accidental sampling (the technique of determining respondents by choosing who happened to be found) through observation in the field were analyzed in deskriftif. Research results showed the perception of foreign tourists against the availability of access and infrastructure Senaru and Sembalun regions hiking track is 67.4% were either satisfied and 26.1% are very satisfied, while local tourists declared satisfied against the conditions, access, facility and Senaru and Sembalun regions hiking paths in the amount of 50% and stating quite satisfied of 50%.Keywords : Mount Rinjani National Park, Climbing Trail, Senaru and Sembalun